TEACHERS’ WORKING CONDITIONS IN TIMES OF PROFESSIONAL CRISIS: EVIDENCE OF POLAND - Kamińska, Małgorzata (The Modern Higher Education Review, 2023)
In the Polish ranking of occupational prestige, the teaching profession enjoys a high level of recognition. The high prestige of the teaching profession in society has been maintained consistently for almost 50 years. It seems that this should be followed by the attractiveness of the profession and the influx of new candidates for pedagogical studies, as well as the high level of availability of teachers in schools. However, it turns out that in Poland and many other European countries, the symptoms of the crisis in the teaching profession are intensifying. More and more teachers resign from their jobs, change their profession and retire. There is a shortage of people willing to train as teachers. There may be many reasons. Teachers’ working conditions (including position, working time and remuneration, form of employment, age of retirement, number of units) are potentially one of the elements describing and determining the perpetuation of disturbing symptoms in individual countries and throughout Europe. The article presents analyses of research results from national and international reports, which confirm the phenomenon of the crisis of the teaching profession. Professional challenges in teachers’ everyday work that affect their mental condition and social and professional well-being were characterized. Detailed analyses of working conditions refer to selected factors – teachers’ remuneration and working time.